2011
DOI: 10.1063/1.3631674
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable Al-doped ZnO transparent conductors using an oxidized ultrathin metal capping layer at its percolation thickness

Abstract: Metal capping layer can be used to enhance the physical properties of thin films. We propose a transparent conductor structure made of Al-doped ZnO (AZO) and an oxidized Ni capping layer, the latter with a thickness in proximity of its percolation threshold (2.5 nm). The capping layer inhibits the penetration of oxygen and water into the AZO’s grain boundaries thus significantly increasing the stability of the combined structure, as it is shown by its resistance in damp heat testing at 95 °C and 95% humidity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…31,32 The stability of the electrical and optical properties of ZnO can be enhanced when preventing a direct exposure of the film to atmosphere by using a moisture diffusion barrier. 33,34 The Al 2 O 3 is known to be an excellent gas diffusion barrier, capable of achieving intrinsic water vapor transmission rates (WVTR) in order of 10 À5 g/m 2 /day when grown by conventional ALD. [35][36][37] A similar value of intrinsic WVTR (10 À5 g/m 2 /day) has been measured for spatial-ALD Al 2 O 3 thin-films grown at $0.2 nm/s and a temperature of C, 85% RH environment.…”
Section: 27mentioning
confidence: 99%
“…31,32 The stability of the electrical and optical properties of ZnO can be enhanced when preventing a direct exposure of the film to atmosphere by using a moisture diffusion barrier. 33,34 The Al 2 O 3 is known to be an excellent gas diffusion barrier, capable of achieving intrinsic water vapor transmission rates (WVTR) in order of 10 À5 g/m 2 /day when grown by conventional ALD. [35][36][37] A similar value of intrinsic WVTR (10 À5 g/m 2 /day) has been measured for spatial-ALD Al 2 O 3 thin-films grown at $0.2 nm/s and a temperature of C, 85% RH environment.…”
Section: 27mentioning
confidence: 99%
“…In fact, capping of DH-sensitive TCOs to improve their stability to heat and humidity is a known effective approach, as demonstrated earlier for ZnO electrodes. 16,34,35 In summary, we have studied the sensitivity to heat and humidity of sputtered ITO, IO:H, IZO, and IO:H/ITO bilayers front contacts used in solar cells by DH test. We found that polycrystalline ITO and amorphous IZO films feature high stability to heat and humidity, thus promising long term stability, needed for large-scale deployment of solar cells, whereas polycrystalline IO:H films degrade under DH exposure.…”
mentioning
confidence: 99%
“…The stability of ZnO:Al can be improved by introduction of barrier layers . In previous work, we have demonstrated damp heat stable ZnO:Al films after annealing under a protective silicon layer, which had been removed before degradation .…”
Section: Introductionmentioning
confidence: 99%